Biologics and Small Molecules in Ulcerative Colitis and Crohn's Disease: Current Evidence and Clinical Relevance - Stephan Vavricka (healthbook TIMES Das Schweizer Ärztejournal Journal Des Médecins Suisses)
The treatment of the chronic inflammatory bowel diseases (IBD) ulcerative colitis and Crohn’s disease has made significant progress with the introduction of biologics and small molecules. In addition to conventional immunosuppressants, targeted modulators of inflammatory pathways – such as TNF-α inhibitors, interleukin inhibitors, integrin antagonists, JAK inhibitors, and S1P receptor modulators – have become integral components of therapy. Clinical studies demonstrate that biologics like adalimumab, infliximab, and vedolizumab significantly improve remission rates, while newer IL-23 and JAK inhibitors offer promising options for therapy-refractory patients. New drug classes such as anti-TL1A antibodies and MiR124 modulators are further expanding the therapeutic spectrum.